ADOLESCENTS PROBLEM RECOGNITION, CONSTRAINT RECOGNITION AND LEVEL OF INVOLVEMENT IN REPRODUCTIVE HEALTH INFORMATION SEEKING AND PROCESSING - Samosir, Ricky Alexander; Hendriyani, Hendriyani (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: As social and sexual being, adolescent have rights to exchange, seek and process information regarding their sexual and reproductive health. However, many adolescent in Indonesia did not seek and process information about reproductive health due to some barriers. Using situational theory of publics in the context of adolescent reproductive health in Indonesia, this study aimed to determine the effect of problem recognition, constraint recognition and level of involvement on information seeking and information processing. Methods: This cross-sectional study was conducted in September until December 2013 among 124 high school students in SMA Angkasa 1 Lanud Medan. Results: This study found that problem recognition, constraint recognition and level of involvement has 14% effect on information seeking with constraint recognition as the independent variable that has the biggest effect (12.1%). Problem recognition, constraint recognition and level of involvement has 9.8% effect on information processing with constraint recognition as the independent variable that has the biggest effect (8.1%). Conclusions: Realizing that constraint recognition had the highest effect both on information seeking and information processing, researcher recommend health communication campaign manager has to reduce adolescentâs constraint recognition in reproductive health, so adolescent can have higher information seeking and processing in reproductive health.Â